GLITCHES ON REALITY OF FINANCIAL SERVICES PROVIDED TO CUSTOMERS IN GHANA - Solomon ARHIN (Business Excellence and Management, 2018)
Provision of financial services and level of customer satisfaction are intricately intertwined, rather than separate concepts. Commercial banking in Ghana requires a lot of improvement as customers continuously err complaints about mediocre services received from different banking locations in the country. Most of the complaints are prevalent pertaining to the high cost of doing business with the financial institutions. Interest charges are very fundamental to any financial institutions and even from biblical perspectives in Matthew 25:14-27. This research measured the performance of three hundred and ninety (390) respondents who were asked to respond to questionnaire on provision of commercial banking services in Ghana and its associated profitability and risks. The respondents had diverse background comprising of sixty-eight (68) financial managers and Three-hundred and twenty-two (322) key customers who are patronizing different services from the commercial banks in Ghana. The findings revealed that majority of the respondents seem to be abreast with the banking operations in Ghana and receive average customer services. Better customer service provision in banks lead to reduction of banks risk while increasing profitability and liquidity. These findings will be relevant theoretically, practically and also assist policy formulators in making strategies about financial institutions. The research concludes that scale economies must be used in the banks to ensure efficient service provision .The study recommends strong policy formulations and implementation from the central authority for financial institutions so that satisfactory performance and service delivery can be used as yardstick to measure and monitor performances of banks and other financial institutions in the country on regular basis.